Simplified Semantics for Further Relevant Logics II: Propositional Constants - Øgaard, Tore Fjetland (Logic and Logical Philosophy, 2024)
It is shown how to model propositional constants within the simplified Routley-Meyer semantics. Various axioms and rules allowing the definition of modal operators, implicative negations, enthymematical conditionals, and propositions expressing various infinite conjunctions and disjunctions are set forth and shown to correspond to specific frame conditions. Two propositional constants which are both often designated as “the Ackermann constant” are shown to capture two such “infinite” propositions: The conjunction of every logical law and the conjunction of every truth –what Anderson and Belnap called the “world” constant.